SISTEM INFORMASI REKOMENDASI BERITA PADA WEBSITE SOLOPOS.COM MENGGUNAKAN ALGORITMA APRIORI - Farhan, Muhammad; Fakhriza, Muhammad; Sinaga, Imam Adlin (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Solopos.com presents reliable news from 2009 until the present day, covering various news categories such as education, sports, automotive, lifestyle, entertainment, business, and technology. With an overwhelming amount of news data, it is essential to establish a governance framework for recommending accessed news categories in order to enhance the business strategies of the company in the field of online news. This can be achieved through the implementation of data mining using the Apriori algorithm, which establishes associations within the data to generate news recommendations based on the accessed news category data. The implementation of news category recommendations using the Apriori algorithm involves creating tabular data with a binary number concept, generating itemsets of news categories based on minimum support values through iterations 1-3, forming association data based on confidence values, and determining the final rules Processing the recommendation of news categories using a minimum support value of 30% and a confidence value of 60% for 84 sample data of news categories obtained from each month within a year resulted in four association rule outcomes with the highest percentage of 71.4% among the total number of users. The Apriori algorithm method can be effectively applied to the news recommendation information system based on the seven news categories obtained from the Solopos.com website, thereby generating association values that can assist the company's strategies in news management. Keyword: Data Mining, Apriori Algorithm, News, Solopos. Abstrak: Solopos.com menyajikan berita terpercaya dari tahun 2009 hingga saat ini dengan beberapa kategori berita seperti pendidikan, olahraga, otomotif, lifestyle, entertainment, bisnis, dan teknologi. Dengan menghasilkan data berita terlalu banyak, perlunya tata kelola rekomendasi kategori berita yang diakses masyarakat guna meningkatkan strategi bisnis perusahaan dalam bidang berita online dengan menerapkan implementasi data mining menggunakan algoritma apriori yang membentuk asosiasi dalam data untuk menghasilkan rekomendasi berita sesuai dengan data akses kategori berita. Implementasi rekomendasi kategori berita menggunakan algoritma apriori dilakukan dengan membentuk data tabular dengan konsep bilangan biner, membuat itemset kategori berita sesuai nilai minimum support dengan iterasi 1-3, membentuk data asosiasi sesuai nilai confidence, dan menentukan rule akhir. Untuk 84 data sample kategori berita yang diperoleh dari setiap bulan dalam setahun, pengolahan rekomendasi kategori berita dengan nilai minimum support 30% dan nilai confidence 60% dapat menghasilkan 4 hasil nilai asosiasi yang memiliki persentase tertinggi yaitu sebesar 71,4% dari jumlah pengaksesnya. Metode algoritma apriori dapat digunakan pada sistem informasi rekomendasi berita berdasarkan 7 kategori berita yang diperoleh dari situs solopos.com dengan menghasilkan nilai asosiasi yang dapat membantu strategi perusahaan dalam pengelolaan berita. Kata kunci: Data Mining, Algoritma Apriori, Berita, Solopos.